PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP LINGKUNGAN KERJA (Studi Kasus Pada Bagian Body Repair PT Nasmoco Kaligawe Semarang) - Lisa Amalia Puspitasari; Wahyu Hidayat (Universitas Diponegoro, 2018)
This study aims to know the effect provided by the work environment, compensation and motivation on the performance of PT Nasmoco Kaligawe Semarang employees in the body repair division.This research is an explanatory type, saturated sampling technique and data collection techniques using questionnaire method. The number of samples used in this study were 64 respondents. This study uses quantitative analysis with validity test, reliability test, correlation coefficient, determination coefficient, simple and multiple regression test, and the significance of T test and F test. The results of this study indicated that the work environment affects employees performance by 57.1%. Compensation affects employees performance by 64.3%. Motivation affects employees performance by 61,4%. While simultaneously the work environment, compensation, and motivation affect employees performance by 75.7% and the remaining 24.3% is influenced by variables other than the work environment, compensation and motivation. It showed that the work environment, compensation, and motivation have a positive and significant effect on employees performance variables individually and together.The advice that can be given is that PT Nasmoco Kaligawe Semarang needs to check the equipment regularly, the company needs to increase the compensation and employees motivation can be raised by recording target assessments for each individual so that the individual gets an appreciation.